2022
DOI: 10.23960/jtep-l.v11i4.601-616
|View full text |Cite
|
Sign up to set email alerts
|

Soil Damage Potential Index Based on Weighting Scoring Analysis and Utilization of Geographical Information Systems

Abstract: Indonesia's population in 2021 will increase by 0.92% from 2020. The increasing population demands the fulfillment of food. Land changes and their consequences indicate land damage. The purpose of the study was to assess the soil damage potential index (SDPI) on the slopes of Mount Argopura through terrain analysis and the use of geographic information system technology. The research was carried out on the slopes of Mount Argopura in 2022. The tools used included a clinometer, a GPS, spectrophotometer, AAS, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This concentration is explained in part by the lack of availability of undeveloped land in Marrakech, which has led to a strong demand for land and opened up investment opportunities in the tourism sector (Kurniawansyah et al, 2023;Stapane et al, 2023). In the eastern part of the study area, a more even spread of tourism investment was observed, originating from land previously used for agricultural purposes (Basuki et al, 2022). The abundance of this category was attributed to the flourishing agricultural activity in the communes of Ghmate, Ourika, and Tamazouzte, where water resources, such as Oued Ourika and Issyl and the tributaries, favour development.…”
Section: Spatial Distribution Of Tourism Investments By Originmentioning
confidence: 92%
“…This concentration is explained in part by the lack of availability of undeveloped land in Marrakech, which has led to a strong demand for land and opened up investment opportunities in the tourism sector (Kurniawansyah et al, 2023;Stapane et al, 2023). In the eastern part of the study area, a more even spread of tourism investment was observed, originating from land previously used for agricultural purposes (Basuki et al, 2022). The abundance of this category was attributed to the flourishing agricultural activity in the communes of Ghmate, Ourika, and Tamazouzte, where water resources, such as Oued Ourika and Issyl and the tributaries, favour development.…”
Section: Spatial Distribution Of Tourism Investments By Originmentioning
confidence: 92%
“…The parameters that have been given dignity are then overlaid. The results of the overlay get a total rating which can then be classified into the IPL class [25], [26], [27], [28]. The total value calculation is performed via the subsequent formula: IPL = (R+L+T+H) x B Information: IPL: Land Potential Index Q: Soil Type R: Slope H: Hydrology L: Lithology B: Disaster Vulnerability…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The land area has decreased by 3% from the previous year (Al-Mukmin et al, 2016). The decline in the area of agricultural land in Indonesia is difficult to avoid due to the influence of population growth and development (Basuki et al, 2022a). In the 1990s, Indonesia was self-sufficient in rice, which has declined until now (Mulyani et al, 2020;Mulyani & Nursyamsi, 2017;Pujiharti, 2017).…”
Section: Introductionmentioning
confidence: 99%